2020
DOI: 10.7150/jca.39717
|View full text |Cite
|
Sign up to set email alerts
|

DNT Cell-based Immunotherapy: Progress and Applications

Abstract: Cancer immunotherapy has firmly established a dominant status in recent years. Adoptive cellular immunotherapy (ACI) is the main branch of immunotherapy. Recently, the immune effector cells of ACI, such as T cells, NK cells, and genetically engineered cells, have been used to achieve significant clinical benefits in the treatment of malignant tumors. However, the clinical applications have limitations, including toxicity, unexpectedly low efficiency, high costs and strict technical requirements. More explorati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 111 publications
(141 reference statements)
1
29
1
Order By: Relevance
“…Given that clinical application of both DNTs and Ide have been tried, application of these findings into clinic might contribute to enhancing the efficacy and durability of response [ 97 ]. What is more, DNTs therapy could significantly reduce lung tumor growth in patient-derived xenograft models but could not eradicate the full extent of the tumor cells [ 98 ].…”
Section: Development and Subgroups Of Dntsmentioning
confidence: 99%
“…Given that clinical application of both DNTs and Ide have been tried, application of these findings into clinic might contribute to enhancing the efficacy and durability of response [ 97 ]. What is more, DNTs therapy could significantly reduce lung tumor growth in patient-derived xenograft models but could not eradicate the full extent of the tumor cells [ 98 ].…”
Section: Development and Subgroups Of Dntsmentioning
confidence: 99%
“…A series of previous studies indicated that DNT cells were predominately memory phenotype in SIV infection, and have a T helper function, secreting CD4-like cytokines (IL-4, IL-17, IFN-γ and TNF-α) in SIV-infected or healthy monkeys such as sooty mangabeys ( 18 20 ). However, most studies identified these cells as similar to regulatory T cells (Tregs), which could suppress T cells, B cells, dendritic cells, and NK cells in graft-versus-host disease, autoimmune diseases, and infectious disease ( 21 23 ). Elevated DNT cells were reported to associate with the control of immune activation in both primary HIV-1 infection and IRs, suggesting the role of DNT cells in disease progression and immune reconstitution of PLWH ( 23 , 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…DNT cells account for 1–3% of total lymphocytes in peripheral blood and play an important role in various diseases' immunopathogenesis [ 14 16 ]. In patients with antineutrophil cytoplasmic autoantibody (ANCA)-associated vasculitis (AAV), the percentage of DNT cells was elevated along with renal damage [ 17 ].…”
Section: Discussionmentioning
confidence: 99%